The Concentrations of Heavy Metals Pb, Cu and Zn in Sea Water and Sediment in Sungai Enam Waters of Bintan Island, Riau Islands Province - Petti Apriani; Bintal Amin; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The Concentrations of Heavy Metals Pb, Cu and Zn in Sea Water and Sediment in Sungai Enam Waters of Bintan Island, Riau Islands Province